Hydrologic and Nutrient Modeling within an Agricultural Watershed in Southeast Kansas - V. J. Alarcon; Gretchen Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2016)
Access to safe, clean water is important to support society. Agricultural watersheds are often contaminated due to agricultural activities. Identification of specific factors contributing to impairment of water bodies is important to target remediation efforts. This research is designed to explore water quality within the Middle Neosho Watershed in southeastern Kansas to make more informed decisions in potential corrective actions.
Keywords: water quality